Corporate Social Performance, Legitimacy, and the Choice of Foreign Partners by State-Controlled Entities in the Global Extractive Industries - Symeou, Pavlos C.; Kassinis, George I. (My University, 2023)
We study the outcome of the decision of a state-controlled entity (SCE) to form an international joint venture (IJV) with a foreign partner in the SCE's country. Focusing on the perspective of the host SCE, we propose that in its search for a partner, the SCE will evaluate the sociopolitical legitimacy effect of a candidate partner's corporate social performance (CSP). Thereby, the SCE will consider CSP an important selection criterion because of its legitimacy effect on the selection decision, the SCE, the IJV, and the host state in the eyes of salient local and international stakeholders. Moreover, the legitimacy effect of a candidate partner's CSP will further influence the decision outcome through its interaction with the level of corruption in the candidate partner's home country, the extant sociopolitical legitimacy of the host state, and the number of neighbouring countries of the host country participating in international multi-stakeholder initiatives. We find support for our hypotheses using a novel sample of extractive industries IJVs between SCEs from 48 countries and 203 foreign partners from 22 countries for the period 2000–15.
Keywords: corporate social performance; extractive industries; international joint ventures; legitimacy; state-controlled entities